The Impact of Student-led Community Health Screenings on Clients’ Health Knowledge and Outcomes: A Qualitative Study in New Zealand - JiaRong Yap; Wendy Wenming Zhai; Cindy Seunghee Pak; Sharon Brownie (Journal of Preventive Medicine and Public Health)
Objectives This study investigated the impact of community health screenings (CHS) on the Asian community, focussing on the role of a student-led health and wellness centre in promoting and improving health outcomes. The CHS is a collaboration between Te Kotahi Oranga | Health and Wellness Centre and The Asian Network Incorporated, offering free health screenings to Asian migrants in the Waikato region, New Zealand. Methods Employing a qualitative approach, we interviewed clients who participated in the CHS to determine their perceptions regarding the effectiveness of the programme, its influence on their health knowledge and actions, and their overall satisfaction with the service. The Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist was used to report the study. Results Data analysis utilising reflexive thematic analysis yielded 5 themes: satisfaction and appreciation for the free health screening; strengthened commitment to better personal health; barriers and challenges in accessing public healthcare services; improved knowledge and awareness of health risks; and provision of more health screening tests and health seminars. The findings highlight the significance of culturally tailored health initiatives in addressing healthcare disparities, emphasising the need for innovative strategies to ensure continuity of care and support for underserved populations. Conclusions This research contributes to the understanding of how student-led health interventions can enhance public health efforts and improve health outcomes in Asian and migrant communities.